Membangun Kesadaran melalui Inovasi Produk Daur Ulang di Tingkat Rumah Tangga - Agus Mulyono; Danang Sunyoto (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aims to enhance public awareness and skills in managing household waste through an innovative recycling-based approach. The main problems identified in the target community include limited understanding of waste segregation, lack of knowledge regarding the economic potential of household waste, and insufficient skills to transform waste materials into useful products. To address these issues, the program was implemented through several stages, including an initial survey to identify community needs, environmental education and awareness sessions, hands-on training on producing recycled products, and continuous mentoring to ensure the sustainability of the activities.The results show a significant increase in participants’ knowledge of proper waste management and recycling concepts. Moreover, the community successfully produced various creative and functional recycled items such as plant pots, household crafts, and other aesthetically valuable products with economic potential. The program also facilitated the establishment of a resident group committed to continuing the initiative independently. Overall, this community service activity demonstrates that practical environmental education can effectively foster ecological awareness, strengthen community participation, and create opportunities for local economic empowerment through the utilization of household waste.